ENSURING ECONOMIC GROWTH BASED ON THE DEVELOPMENT OF THE DIGITAL ECONOMY - Vaydullayev Ilyos Hamidulla o'g'li (American Journals, 2024)
This article presents the rationale for ensuring sustainable economic growth in the country based on the innovative development of industry in the context of the digital economy. Economic development, especially in the industrial sectors, the existing problems in the development of the innovative environment were studied and analyzed. Also, analysis of the state of production of industrial products by types of economic activity in our country, its share in the gross domestic product and export was carried out. In addition, scientifically based proposals for innovative development of the industry have been developed.
Keywords: Digital economy, industry, economic growth, socio-economic development, innovation, technology.